A preparation method of silicone stone sealant

By modifying the vapor phase silica using a silane coupling agent containing double bonds in the silicone stone sealant, and adding anti-mold and hydrophobic modifiers, the problem of silicone sealant being susceptible to mold erosion in humid environments is solved. , achieving excellent mechanical, mildew-proof and superhydrophobic properties.

CN118755442BActive Publication Date: 2025-02-18GUANGZHOU BAORUI NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410914142.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-09
Publication Date
2025-02-18
Estimated Expiration
2044-07-09

AI Technical Summary

Technical Problem

Silicone sealant is susceptible to mold erosion in humid environments, causing the colloid to turn black and damage, and lose its sealing and bonding function. The prior art solves this problem by adding anti-mold agents, but there are adverse effects on the migration, escape of anti-mold agents and their mechanical properties.

Method used

The gas-phase silica is treated with a silane coupling agent containing double bonds, modified the double bond, then added methacrylic acid for polymerization, and finally dimethyloctadecyl[3-(trimethoxysilyl)propyl Ammonium chloride is used as a mildew anti-mold agent and long-chain alkyl alcohol as a hydrophobic modifier. Modified vapor phase silica is prepared by dehydration and condensation reaction, thereby preparing silicone stone sealant with excellent mechanical and mildew anti-mold properties.

Benefits of technology

This method not only improves the mechanical properties and anti-mold properties of silicone stone sealant, but also provides it with superhydrophobic properties, especially in humid environments to effectively maintain the dryness of the colloid and prevent mold growth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004934589200000121
    Figure BDA0004934589200000121
Patent Text Reader

Abstract

The present invention relates to a preparation method of a silicone stone sealant, and belongs to the technical field of sealants. The present invention creatively improves reinforcing fillers, firstly uses a silane coupling agent containing double bonds to treat fumed silica, modifies the double bonds through the action of silane alkoxy and silanol, then adds methacrylic acid to polymerize the double bonds, modifies the polymer, and finally adds dimethyl octadecyl [3-(trimethoxysilyl)propyl] ammonium chloride as a mildew inhibitor and a long-chain alkyl alcohol as a hydrophobic modifier, thereby utilizing carboxyl and hydroxyl groups for dehydration condensation, thereby preparing a modified fumed silica, and the silicone stone sealant obtained by mixing it with other components not only has excellent mechanical properties and mildew-proof properties when actually used, and the mildew inhibitor is not easy to migrate and escape, but also has super-hydrophobic properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sealants, and in particular relates to a method for preparing a silicone stone sealant. Background Art

[0002] Stone glue, also known as stone adhesive, refers to various glue products used in the process of stone from processing to use (repair, reinforcement, compounding, bonding, maintenance, etc.). Among them, silicone sealant has been widely used as a stone adhesive due to its good heat resistance and weather resistance. However, since silicone sealant itself does not have a mildew-proof effect, it is very susceptible to mildew erosion during actual use, resulting in blackening of the colloid or even damage, and loss of sealing and bonding functions. The problem is more prominent when used in a humid environment. In order to solve this technical defect, many existing technologies will add additional mildew inhibitors to give silicone sealants excellent mildew-proof effects. , such as adding dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, however, this technology still has disadvantages that limit its application. This is because dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride has methoxy groups. In addition to being a mildew inhibitor, it is also equivalent to a cross-linking agent, which can participate in the curing in the system. Although the problem of migration and escape of small molecules of quaternary ammonium salts in silicone materials can be well solved after curing, in order to achieve excellent mildew prevention effects, too much mildew inhibitor is often added, resulting in "excess" methoxy groups, which hinders the formation of network cross-linking points. The "excess" methoxy groups play a chain extension role, which has an adverse effect on the mechanical properties. Summary of the invention

[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing a silicone stone sealant. The present invention creatively improves the reinforcing filler, firstly uses a silane coupling agent containing double bonds to treat fumed silica, and modifies the double bonds through the action of silane alkoxy and silanol groups, then adds methacrylic acid to polymerize the double bonds and modify the polymer, and finally adds dimethyl octadecyl [3-(trimethoxysilyl)propyl] ammonium chloride as a mildew inhibitor and a long-chain alkyl alcohol as a hydrophobic modifier, thereby utilizing carboxyl and hydroxyl groups for dehydration condensation, thereby preparing a modified fumed silica, and the silicone stone sealant obtained by mixing the fumed silica with other components not only has excellent mechanical properties and mildew inhibitory properties when actually used, and the mildew inhibitor is not easy to migrate and escape, but also has super hydrophobic properties.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for preparing a silicone stone sealant, the method comprising the following steps:

[0006] Step A: Under vacuum, α, ω-dihydroxy polysiloxane and dimethyl silicone oil are stirred at a speed of 800-1000 r / min for 20-30 minutes, and then modified fumed silica and silane coupling agent are added, and the stirring is continued for 5-10 minutes. Finally, a cross-linking agent and a catalyst are added, and the mixture is stirred for 15-20 minutes. The mixture is sealed and stored, and the preparation is completed.

[0007] As a preferred technical solution of the present invention, the vacuum degree of the vacuum state in step A is -0.095MPa.

[0008] As a preferred technical solution of the present invention, the viscosity of the α,ω-dihydroxy polysiloxane in step A is 20000-50000 mPa·s at 25° C., and the amount of the α,ω-dihydroxy polysiloxane used is 90-100 parts by weight.

[0009] As a preferred technical solution of the present invention, the viscosity of the dimethyl silicone oil in step A is 300-500 mPa·s at 25° C., and the amount of the dimethyl silicone oil is 15-20 parts by weight.

[0010] As a preferred technical solution of the present invention, the amount of the modified fumed silica in step A is 10-12 parts by weight.

[0011] As a preferred technical solution of the present invention, the modified fumed silica in step A is prepared by the following steps:

[0012] Step (1): adding 5-7 parts by weight of fumed silica and 0.5-1 parts by weight of deionized water to 80-100 parts by weight of anhydrous ethanol, stirring for 5-10 minutes at room temperature, then adding 1-1.5 parts by weight of a double bond silane coupling agent, stirring for 8-10 hours at 70-75° C., filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 50-80° C. until constant weight, to obtain double bond modified fumed silica;

[0013] Step (2): adding the double bond modified fumed silica, 8-10 parts by weight of methacrylic acid and 0.1-0.3 parts by weight of an initiator to 80-100 parts by weight of deionized water, stirring at 75-80° C. for 5-7 hours, filtering, removing the filtrate, washing with deionized water, and finally vacuum drying at 50-80° C. until constant weight, to obtain polymer modified fumed silica;

[0014] Step (3): Add the polymer-modified fumed silica and 2-4 parts by weight of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride to 60-70 parts by weight of anhydrous ethanol, stir and mix at room temperature for 5-10 minutes, then adjust the pH with concentrated sulfuric acid, stir at 70-75°C for 3-4 hours under ultrasound, then add 2-2.5 parts by weight of a long-chain alkyl alcohol, continue stirring for 1.5-2 hours, filter, remove the filtrate, wash with anhydrous ethanol, and finally vacuum dry at 50-80°C until constant weight, and the preparation is completed.

[0015] Furthermore, the double bond silane coupling agent in step (1) is at least one of vinyltrimethoxysilane and vinyltriethoxysilane.

[0016] Furthermore, the initiator in step (2) is potassium persulfate.

[0017] Furthermore, the mass fraction of the concentrated sulfuric acid in step (3) is 70-75%.

[0018] Furthermore, the pH adjustment in step (3) refers to adjusting the pH to 2-3.

[0019] Furthermore, the power of the ultrasound in step (3) is 300-400W.

[0020] Furthermore, the long-chain alkyl alcohol in step (3) is stearyl alcohol.

[0021] As a preferred technical solution of the present invention, the silane coupling agent in step A is at least one of γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane, and the amount of the silane coupling agent is 1-2 parts by weight.

[0022] As a preferred technical solution of the present invention, the cross-linking agent in step A is at least one of tetraethoxysilane and methyltrimethoxysilane, and the amount of the cross-linking agent is 8-10 parts by weight.

[0023] As a preferred technical solution of the present invention, the catalyst in step A is dibutyltin dilaurate, and the amount of the catalyst is 0.4-0.6 parts by weight.

[0024] Beneficial effects of the present invention:

[0025] (1) The present invention creatively improves the reinforcing filler. First, the fumed silica is treated with a silane coupling agent containing double bonds, and the double bonds are modified by the action of silane alkoxy and silanol groups. Then, methacrylic acid is added to polymerize the double bonds to modify the polymer. Finally, dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride is added as a mildew inhibitor and a long-chain alkyl alcohol is added as a hydrophobic modifier. The carboxyl group and the hydroxyl group are used for dehydration condensation to prepare a modified fumed silica. The silicone stone sealant obtained by mixing the fumed silica with other components has excellent mechanical properties and mildew resistance when actually used, and the mildew inhibitor is not easy to migrate or escape, and has super hydrophobic properties.

[0026] (2) The present invention creatively utilizes a silane coupling agent containing double bonds to treat fumed silica, and then modifies the double bonds through the action of silaneoxy and silanol groups, and then adds methacrylic acid to polymerize the double bonds and modify the polymer. On the one hand, the polymer structure on the surface of the reinforcing filler and the cured organic silicon network structure can form a strong molecular chain entanglement, thereby increasing the intermolecular force, promoting the combination of the inorganic phase and the organic phase, and better exerting the reinforcing effect of the reinforcing filler to improve the mechanical properties. On the other hand, the polymer structure contains carboxyl groups, which can provide a reaction platform for the subsequent reaction. When dimethyloctadecyl [3-(trimethoxysilyl)propyl] ammonium chloride is used as a mildew inhibitor and a long-chain alkyl alcohol is used as a hydrophobic modifier, dehydration condensation can be carried out through the action of carboxyl and hydroxyl groups (the methoxy group of the mildew inhibitor will be hydrolyzed and generate hydroxyl groups when it encounters water), thereby loading the quaternary ammonium salt small molecules and long-chain alkanes onto the surface of the reinforcing filler, giving the silicone stone sealant excellent mildew resistance and super hydrophobic properties.

[0027] (3) Compared with the prior art, the present invention loads dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride onto the surface of the reinforcing filler, but does not solidify it into the network structure of the silicone, thereby solving the problem of migration and escape of small molecules of quaternary ammonium salt in the silicone material. At the same time, the mildew inhibitor not only does not have an adverse effect on the mechanical properties, but also promotes the mechanical properties after being bonded to the polymer structure. In addition, due to the increase in the number of hydrophilic groups on the surface of the reinforcing filler, the present invention also adds a certain amount of long-chain alkyl alcohol as a hydrophobic modifier, which, on the one hand, forms more hydrophobic ends, improves hydrophobicity, and further promotes mildew resistance. In particular, in a humid environment, the sealant can better maintain the "dryness" of the colloid and is not easily "adhered" to water, thereby restricting the growth of mold. On the other hand, it further promotes the entanglement of the polymer structure and the silicone network structure, thereby better improving the mechanical properties. DETAILED DESCRIPTION

[0028] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0029] The fumed silica in all the embodiments and comparative examples of the present invention was purchased directly from the market, and was purchased from Hubei Huifu Nanomaterial Co., Ltd., with a model of HL-200.

[0030] Example 1

[0031] A method for preparing a silicone stone sealant, the method comprising the following steps:

[0032] Step A: Under vacuum, α, ω-dihydroxy polysiloxane and dimethyl silicone oil are stirred at a speed of 800 r / min for 20 minutes, and then modified fumed silica and silane coupling agent are added, and stirring is continued for 5 minutes. Finally, a cross-linking agent and a catalyst are added, and stirring is continued for 15 minutes. The mixture is sealed and stored, and the preparation is completed.

[0033] The vacuum degree of the vacuum state in step A is -0.095 MPa.

[0034] The viscosity of the α,ω-dihydroxy polysiloxane in step A is 20000 mPa·s at 25° C., and the amount of the α,ω-dihydroxy polysiloxane used is 90 parts by weight.

[0035] The viscosity of the dimethyl silicone oil in step A is 300 mPa·s at 25° C., and the amount of the dimethyl silicone oil used is 15 parts by weight.

[0036] The amount of modified fumed silica used in step A is 10 parts by weight.

[0037] The modified fumed silica described in step A is prepared by the following steps:

[0038] Step (1): adding 5 parts by weight of fumed silica and 0.5 parts by weight of deionized water to 80 parts by weight of anhydrous ethanol, stirring at room temperature for 5 minutes, then adding 1 part by weight of a double bond silane coupling agent, stirring at 70° C. for 8 hours, filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 50° C. until constant weight, to obtain double bond modified fumed silica;

[0039] Step (2): adding the double bond modified fumed silica, 8 parts by weight of methacrylic acid and 0.1 parts by weight of an initiator to 80 parts by weight of deionized water, stirring at 75° C. for 5 hours, filtering, removing the filtrate, washing with deionized water, and finally vacuum drying at 50° C. until constant weight, to obtain polymer modified fumed silica;

[0040] Step (3): Add the polymer-modified fumed silica and 2 parts by weight of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride to 60 parts by weight of anhydrous ethanol, stir and mix at room temperature for 5 minutes, then adjust the pH with concentrated sulfuric acid, stir at 70°C for 3 hours under ultrasound, then add 2 parts by weight of a long-chain alkyl alcohol, continue stirring for 1.5 hours, filter, remove the filtrate, wash with anhydrous ethanol, and finally vacuum dry at 50°C until constant weight, and the preparation is completed.

[0041] The double bond silane coupling agent in step (1) is vinyltrimethoxysilane.

[0042] The initiator in step (2) is potassium persulfate.

[0043] The mass fraction of the concentrated sulfuric acid in step (3) is 70%.

[0044] The pH adjustment in step (3) refers to adjusting the pH to 2.

[0045] The power of the ultrasound in step (3) is 300W.

[0046] The long-chain alkyl alcohol in step (3) is stearyl alcohol.

[0047] The silane coupling agent in step A is γ-aminopropyltrimethoxysilane, and the amount of the silane coupling agent is 1 part by weight.

[0048] The crosslinking agent in step A is tetraethoxysilane, and the amount of the crosslinking agent used is 8 parts by weight.

[0049] The catalyst in step A is dibutyltin dilaurate, and the amount of the catalyst used is 0.4 parts by weight.

[0050] Example 2

[0051] A method for preparing a silicone stone sealant, the method comprising the following steps:

[0052] Step A: Under vacuum, α, ω-dihydroxy polysiloxane and dimethyl silicone oil are stirred at a speed of 1000 r / min for 30 minutes, and then modified fumed silica and silane coupling agent are added, and stirring is continued for 10 minutes. Finally, a cross-linking agent and a catalyst are added, and stirring is continued for 20 minutes. The mixture is sealed and stored, and the preparation is completed.

[0053] The vacuum degree of the vacuum state in step A is -0.095 MPa.

[0054] The viscosity of the α,ω-dihydroxy polysiloxane in step A is 50000 mPa·s at 25° C., and the amount of the α,ω-dihydroxy polysiloxane used is 100 parts by weight.

[0055] The viscosity of the dimethyl silicone oil in step A is 500 mPa·s at 25° C., and the amount of the dimethyl silicone oil used is 20 parts by weight.

[0056] The amount of modified fumed silica used in step A is 12 parts by weight.

[0057] The modified fumed silica described in step A is prepared by the following steps:

[0058] Step (1): adding 7 parts by weight of fumed silica and 1 part by weight of deionized water to 100 parts by weight of anhydrous ethanol, stirring at room temperature for 10 minutes, then adding 1.5 parts by weight of a double bond silane coupling agent, stirring at 75° C. for 10 hours, filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 80° C. until constant weight, to obtain double bond modified fumed silica;

[0059] Step (2): adding the double bond modified fumed silica, 10 parts by weight of methacrylic acid and 0.3 parts by weight of an initiator to 100 parts by weight of deionized water, stirring at 80° C. for 7 hours, filtering, removing the filtrate, washing with deionized water, and finally vacuum drying at 80° C. until constant weight, to obtain polymer modified fumed silica;

[0060] Step (3): Add the polymer-modified fumed silica and 4 parts by weight of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride to 70 parts by weight of anhydrous ethanol, stir and mix at room temperature for 10 minutes, then adjust the pH with concentrated sulfuric acid, stir at 75°C for 4 hours under ultrasound, then add 2.5 parts by weight of a long-chain alkyl alcohol, continue stirring for 2 hours, filter, remove the filtrate, wash with anhydrous ethanol, and finally vacuum dry at 80°C until constant weight, and the preparation is completed.

[0061] The double bond silane coupling agent in step (1) is vinyltrimethoxysilane.

[0062] The initiator in step (2) is potassium persulfate.

[0063] The mass fraction of the concentrated sulfuric acid in step (3) is 75%.

[0064] The pH adjustment in step (3) refers to adjusting the pH to 3.

[0065] The power of the ultrasound in step (3) is 400W.

[0066] The long-chain alkyl alcohol in step (3) is stearyl alcohol.

[0067] The silane coupling agent in step A is γ-aminopropyltrimethoxysilane, and the amount of the silane coupling agent is 2 parts by weight.

[0068] The crosslinking agent in step A is tetraethoxysilane, and the amount of the crosslinking agent used is 10 parts by weight.

[0069] The catalyst in step A is dibutyltin dilaurate, and the amount of the catalyst used is 0.6 parts by weight.

[0070] Example 3

[0071] A method for preparing a silicone stone sealant, the method comprising the following steps:

[0072] Step A: Under vacuum, α, ω-dihydroxy polysiloxane and dimethyl silicone oil are stirred at a speed of 900 r / min for 25 minutes, and then modified fumed silica and silane coupling agent are added, and stirring is continued for 8 minutes. Finally, a cross-linking agent and a catalyst are added, and stirring is continued for 18 minutes. The mixture is sealed and stored, and the preparation is completed.

[0073] The vacuum degree of the vacuum state in step A is -0.095 MPa.

[0074] The viscosity of the α,ω-dihydroxy polysiloxane in step A is 30000 mPa·s at 25° C., and the amount of the α,ω-dihydroxy polysiloxane used is 95 parts by weight.

[0075] The viscosity of the dimethyl silicone oil in step A is 400 mPa·s at 25° C., and the amount of the dimethyl silicone oil used is 18 parts by weight.

[0076] The amount of modified fumed silica used in step A is 11 parts by weight.

[0077] The modified fumed silica described in step A is prepared by the following steps:

[0078] Step (1): adding 6 parts by weight of fumed silica and 0.8 parts by weight of deionized water to 90 parts by weight of anhydrous ethanol, stirring at room temperature for 8 minutes, then adding 1.3 parts by weight of a double bond silane coupling agent, stirring at 73° C. for 9 hours, filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 70° C. until constant weight, to obtain double bond modified fumed silica;

[0079] Step (2): adding the double bond modified fumed silica, 9 parts by weight of methacrylic acid and 0.2 parts by weight of an initiator to 90 parts by weight of deionized water, stirring at 78° C. for 6 hours, filtering, removing the filtrate, washing with deionized water, and finally vacuum drying at 70° C. until constant weight, to obtain polymer modified fumed silica;

[0080] Step (3): Add the polymer-modified fumed silica and 3 parts by weight of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride to 65 parts by weight of anhydrous ethanol, stir and mix at room temperature for 8 minutes, then adjust the pH with concentrated sulfuric acid, stir at 73°C for 3.5 hours under ultrasound, then add 2.3 parts by weight of a long-chain alkyl alcohol, continue stirring for 1.8 hours, filter, remove the filtrate, wash with anhydrous ethanol, and finally vacuum dry at 70°C until constant weight, and the preparation is completed.

[0081] The double bond silane coupling agent in step (1) is vinyltrimethoxysilane.

[0082] The initiator in step (2) is potassium persulfate.

[0083] The mass fraction of the concentrated sulfuric acid in step (3) is 73%.

[0084] The pH adjustment in step (3) refers to adjusting the pH to 2.5.

[0085] The power of the ultrasound in step (3) is 350W.

[0086] The long-chain alkyl alcohol in step (3) is stearyl alcohol.

[0087] The silane coupling agent in step A is γ-aminopropyltrimethoxysilane, and the amount of the silane coupling agent is 1.5 parts by weight.

[0088] The crosslinking agent in step A is tetraethoxysilane, and the amount of the crosslinking agent used is 9 parts by weight.

[0089] The catalyst in step A is dibutyltin dilaurate, and the amount of the catalyst used is 0.5 parts by weight.

[0090] Comparative Example 1

[0091] Based on Example 1, no long-chain alkyl alcohol is added in step (3), and the rest remain unchanged.

[0092] Comparative Example 2

[0093] On the basis of Example 1, the amount of methacrylic acid in step (2) was changed to 4 parts by weight, and the rest remained unchanged.

[0094] Comparative Example 3

[0095] On the basis of Example 1, step A is changed to: in a vacuum state, α, ω-dihydroxy polysiloxane and dimethyl silicone oil are stirred at a speed of 800 r / min for 20 minutes, then the modified fumed silica and silane coupling agent are added, and the stirring is continued for 5 minutes, and finally the cross-linking agent, catalyst and 4 parts by weight of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride are added, and the mixture is stirred for 15 minutes, and the mixture is sealed and stored, and the preparation is completed; step (3) is changed to: adding the polymer-modified fumed silica to 60 parts by weight of anhydrous ethanol, stirring for 5 minutes at room temperature, and then adjusting the pH with concentrated sulfuric acid, and then adding 2 parts by weight of long-chain alkyl alcohol, stirring at 70°C for 1.5 hours under ultrasound, filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 50°C until constant weight, and the preparation is completed; the rest remain unchanged.

[0096] Comparative Example 4

[0097] On the basis of Example 1, step (3) is changed to adding the polymer-modified fumed silica to 60 parts by weight of anhydrous ethanol, stirring for 5 minutes at room temperature, then adjusting the pH with concentrated sulfuric acid, adding 2 parts by weight of a long-chain alkyl alcohol, stirring for 1.5 hours at 70°C under ultrasound, filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 50°C until constant weight, that is, the preparation is completed; the rest remains unchanged.

[0098] Test Example 1:

[0099] Mechanical properties test:

[0100] The silicone stone sealants prepared in Examples 1-3 and Comparative Examples 1-4 were respectively subjected to tensile strength tests according to standard GB / T 528-2009 to illustrate the mechanical properties.

[0101] Table 1. Mechanical properties test results

[0102] Tensile strength / MPa Example 1 2.49 Example 2 2.57 Example 3 2.52 Comparative Example 1 2.34 Comparative Example 2 2.25 Comparative Example 3 2.00 Comparative Example 4 2.31

[0103] Test Example 2:

[0104] Hydrophobic performance test:

[0105] The silicone stone sealants prepared in Examples 1-3 and Comparative Examples 1-4 were coated respectively, and after being completely cured, the static contact angle and the rolling contact angle were tested, and the test liquid was deionized water.

[0106] Table 2. Hydrophobic performance test results

[0107] Static contact angle / degree Rolling contact angle / degree Example 1 151 9 Example 2 154 8 Example 3 153 8 Comparative Example 1 110 61 Comparative Example 2 155 8 Comparative Example 3 145 14 Comparative Example 4 149 10

[0108] Test Example 3:

[0109] Anti-mildew test:

[0110] The silicone stone sealants prepared in Examples 1-3 and Comparative Examples 1-4 were respectively subjected to a mildew resistance (anti-fungal performance) test with reference to standard QB / T 2591-2003, wherein the fungus species was Aspergillus niger. At the same time, escape and migration tests were also performed accordingly, that is, the tested samples were naturally placed for 180 days, washed with deionized water, and then naturally dried to constant weight, and then the above-mentioned mildew resistance test was performed.

[0111] Table 3. Anti-mildew test results

[0112]

[0113] Comparison between Example 1 and Comparative Examples 1-4 shows that:

[0114] The difference between Comparative Example 1 and Example 1 is that the modified fumed silica is not modified by adding long-chain alkyl alcohol.

[0115] The difference between Comparative Example 2 and Example 1 is that the amount of methacrylic acid used in the modified fumed silica is reduced, that is, the degree of polymerization of the polymer is reduced.

[0116] The difference between Comparative Example 3 and Example 1 is that dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride is not loaded into the modified fumed silica, but participates in the curing.

[0117] The difference between Comparative Example 4 and Example 1 is that the modified fumed silica is not modified by adding dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride.

[0118] From the comparison of test examples 1-3 and example 1 and comparative examples 1-4, it can be seen that only the silicone stone sealant prepared by the present invention can maintain the super-hydrophobic property and obtain excellent mechanical properties and mildew resistance. At the same time, the mildew resistance is not easy to migrate or escape.

[0119] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a silicone stone sealant, characterized in that: The preparation method comprises the following steps: Step A: Under vacuum, α,ω-dihydroxy polysiloxane and dimethyl silicone oil are stirred at a speed of 800-1000 r / min for 20-30 min, and then modified fumed silica and silane coupling agent are added, and the stirring is continued for 5-10 min. Finally, a cross-linking agent and a catalyst are added, and the mixture is stirred for 15-20 min. The mixture is sealed and stored, and the preparation is completed; The modified fumed silica described in step A is prepared by the following steps: Step (1): adding 5-7 parts by weight of fumed silica and 0.5-1 parts by weight of deionized water to 80-100 parts by weight of anhydrous ethanol, stirring for 5-10 minutes at room temperature, then adding 1-1.5 parts by weight of a double bond silane coupling agent, stirring for 8-10 hours at 70-75° C., filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 50-80° C. until constant weight, to obtain double bond modified fumed silica; Step (2): adding the double bond modified fumed silica, 8-10 parts by weight of methacrylic acid and 0.1-0.3 parts by weight of an initiator to 80-100 parts by weight of deionized water, stirring at 75-80° C. for 5-7 hours, filtering, removing the filtrate, washing with deionized water, and finally vacuum drying at 50-80° C. until constant weight, to obtain polymer modified fumed silica; Step (3): Add the polymer-modified fumed silica and 2-4 parts by weight of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride to 60-70 parts by weight of anhydrous ethanol, stir and mix at room temperature for 5-10 minutes, then adjust the pH with concentrated sulfuric acid, stir at 70-75°C for 3-4 hours under ultrasound, then add 2-2.5 parts by weight of a long-chain alkyl alcohol, continue stirring for 1.5-2 hours, filter, remove the filtrate, wash with anhydrous ethanol, and finally vacuum dry at 50-80°C until constant weight, and the preparation is completed.

2. The method for preparing a silicone stone sealant according to claim 1, characterized in that: The viscosity of the α,ω-dihydroxy polysiloxane in step A is 20000-50000 mPa·s at 25° C., and the amount of the α,ω-dihydroxy polysiloxane used is 90-100 parts by weight.

3. The method for preparing a silicone stone sealant according to claim 1, characterized in that: The viscosity of the dimethyl silicone oil in step A is 300-500 mPa·s at 25° C., and the amount of the dimethyl silicone oil used is 15-20 parts by weight.

4. The method for preparing a silicone stone sealant according to claim 1, characterized in that: The amount of the modified fumed silica used in step A is 10-12 parts by weight.

5. The method for preparing a silicone stone sealant according to claim 1, characterized in that: The double bond silane coupling agent in step (1) is at least one of vinyl trimethoxy silane and vinyl triethoxy silane.

6. The method for preparing a silicone stone sealant according to claim 1, characterized in that: The long-chain alkyl alcohol in step (3) is stearyl alcohol.

7. The method for preparing a silicone stone sealant according to claim 1, characterized in that: In step A, the silane coupling agent is at least one of γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane, and the amount of the silane coupling agent is 1-2 parts by weight.

8. The method for preparing a silicone stone sealant according to claim 1, characterized in that: In step A, the cross-linking agent is at least one of tetraethoxysilane and methyltrimethoxysilane, and the amount of the cross-linking agent is 8-10 parts by weight.

9. The method for preparing a silicone stone sealant according to claim 1, characterized in that: The catalyst in step A is dibutyltin dilaurate, and the amount of the catalyst used is 0.4-0.6 parts by weight.

Citation Information

Patent Citations

  • Neutral silicone sealant for stone material and making method thereof

    CN1371953A